2017
DOI: 10.1177/1350650117713435
|View full text |Cite
|
Sign up to set email alerts
|

Wear performance of cylinder liner surface texturing on cylinder liner–piston ring assembly

Abstract: The microgeometrical structure has a great impact on lubricating performance of the cylinder liner–piston ring assembly. Extensive investigations have been done upon the various texture types for better lubrication. However, rarely do they focus on the morphological alteration of the friction surfaces during the initial wearing process. In this study, the pits and grooves at the liner inner surface are processed and experiments are conducted to investigate the influence of the surface texturing structure on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The effects of tests obtained using a real engine powered by an electric motor are better and similar to those of a fired engine than those obtained from reciprocating sliding. In [ 101 , 102 , 103 ], it was found that cavities of a large depth (0.2–0.3 mm) on the liner surface led to less wear, a tendency to scuff, and a coefficient of friction than on the untextured surface. Yin et al [ 104 ] recommended a square dimple array with a tribological behavior was better than the stagger array when rows of dimples were shifted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of tests obtained using a real engine powered by an electric motor are better and similar to those of a fired engine than those obtained from reciprocating sliding. In [ 101 , 102 , 103 ], it was found that cavities of a large depth (0.2–0.3 mm) on the liner surface led to less wear, a tendency to scuff, and a coefficient of friction than on the untextured surface. Yin et al [ 104 ] recommended a square dimple array with a tribological behavior was better than the stagger array when rows of dimples were shifted.…”
Section: Discussionmentioning
confidence: 99%
“…Peng and Huang [ 102 ] powered the real engine with an electric motor to ensure conditions similar to those of the real engine. Cylinder liner B had grooves of comparatively high depth (0.3 mm, width 3 mm), cylinder liner C had isolated dimples of similar depth and diameter of 1 mm, while cylinder liner D had a combination of grooves and dimples ( Figure 12 ).…”
Section: Functional Performance Of Textured Cylinder Liner Surfacesmentioning
confidence: 99%
“…The cylinder liner internal surfaces were processed with five TGT of different depths (50,100,150,200 and 250 mm) by ultraprecision machining technology, which are symmetrically distributed on the internal surface. The width of TGT is 3 mm, with surface occupancy of approximately 12.63 per cent (Wang et al, 2018;Peng and Huang, 2018); see Figure 1.…”
Section: Test Materialsmentioning
confidence: 99%
“…The friction and wear performance can improve via the surface texturing method. [1][2][3] For example, Costa et al 4 pointed out that surface textures hold great potential to enhance the frictional performance of tribological systems. Marian et al 5 used numerical approaches to optimize the micro-textures to further improve tribological properties of the textured surface.…”
Section: Introductionmentioning
confidence: 99%